Strategi Komunikasi Dalam Menciptakan Manajemen Relasi Pada Program Sosialisasi Humas PT. KCIC - Nauli, Kezia; Wardasari, Nilam (Tuturlogi: Journal of Southeast Asian Communication, 2022)
PT. KCIC's Public Relations has completed the socialization to the land excavation residents with the hope that the residents would be informed, understand, and support the development of the Jakarta-Bandung high-speed train. However, in reality, the land excavation residents staged a protest in front of the Istana Merdeka building.. In this research, the author employs a constructivist paradigm with a qualitative comparative approach. The research findings indicate that PT. KCIC used different communication strategies in the socialization of the Jakarta-Bandung high-speed train construction before and after the protest. In the pre-protest communication planning, PT. KCIC focused solely on the company's objectives without understanding the community's conditions. The residents' protest significantly influenced PT. KCIC's choice and determination of communication strategies. After the protest, PT. KCIC began adopting various approaches towards the residents, wrapped in numerous intensive activities and interactions between the residents and PT. KCIC. The approaches employed by PT. KCIC's Public Relations post-protest included educational approaches, non-formal external approaches, and persuasive communication approaches conducted directly by PT. KCIC's Public Relations. PT. KCIC strives to be cooperative and offer solutions to address any community concerns related to the Jakarta-Bandung high-speed train construction. This effort aims to establish a positive relationship between PT. KCIC and the land excavation residents.